Stillbirth rate and maternal risk factors for antenatal stillbirth in Bihar: A hospital-based cross-sectional study - Monika Gupta; Meena Samant; Jayoti Malhotra; Prit Pal Singh (Journal of Family Medicine and Primary Care, 2025)
Background and Objectives: The prevalence and risk factors of stillbirths vary across geographical and socioeconomic contexts, extending beyond maternal and fetal factors. Many of these risks are preventable with quality pregnancy care. Prevention relies on recognizing and appropriately addressing these factors. Methods: This was a descriptive cross-sectional study done at a referral hospital, Patna, Bihar in 2023–2024. All pregnancies complicated with stillbirths were included. Data regarding demographic details, chief complaints, comorbidities, clinical, and laboratory parameters were collected and analyzed in MS Excel. Results: The study involved 5666 deliveries, noting 76 stillbirths (SBR of 13.4/1000 births). Most affected women were aged 25–35 (63%) and from rural areas (70%), with low education (42% up to middle school). Majority belonged to a low socioeconomic class. Few had consanguineous marriages (4%). Primigravida accounted for 52.6%, with inadequate antenatal visits (68%). Stillbirths mostly occurred between 30th and 37th weeks and were associated with pregnancy complications like hypertension (19.7%) and oligohydramnios (48.68%). Female fetuses numbered 41, with 50% showing intrauterine growth retardation. Complaints mainly included decreased fetal movement (66%) and abdominal pain (43%), sometimes occurring together (24%). Conclusion: The study reveals a higher stillbirth rate despite improved education among lower-income women. Pregnancy-related hypertension is a significant risk factor associated with IUGR. Poor antenatal care, healthcare gaps, and limited awareness in rural areas contribute to hypertension-related complications and stillbirths. High uterine rupture rates likely due to delayed diagnosis highlight the need for improved maternal–fetal health awareness, better rural healthcare, and strong societal and political commitment to pregnancy management goals.